The immunological characteristics of TSPAN1 expressing B cells in autoimmune hepatitis - Ou, Yiyan; Chen, Ruiling; Qian, Qiwei; Cui, Nana; Miao, Qi; Tang, Ruqi; You, Zhengrui; Ma, Xiong; Wang, Qixia (Frontiers in Immunology, 2022)
Tetraspanin proteins are closely related to the functional changes of B cells, including antigen presentation, production of cytokines, and transduction. We aim to explore the potential role of Tetraspanin 1 (TSPAN1) in the biological activities of B cells in AIH. Herein, this study found that numbers of cells expressing TSPAN1 were significantly increased in AIH patients compared to PBC, chronic hepatitis B, and healthy control (P < 0.0001). Moreover, there was a positive correlation between numbers of TSPAN1+ cells and AIH disease severity (P < 0.0001). Immunofluorescence staining further confirmed that TSPAN1 was primarily expressed on CD19+ B cells. Flow-cytometric analysis showed that TSPAN1+ B cells secreted more inflammatory cytokines and expressed higher level of CD86 than TSPAN1- B cells. Furthermore, compared with TSAPN1- cells, the expression of CXCR3 on TSPAN1+ cells was also higher. Meanwhile, CXCL10, the ligand of CXCR3, was significantly elevated in the liver of AIH (P < 0.01) and had positive correlation with the quantities of TSPAN1 (P < 0.05). Interestingly, the numbers of TSPAN1+ B cells were decreased in AIH patients after immunosuppressive therapy. Conclusions: TSPAN1+ B cells in the liver may promote the progression of AIH via secreting cytokines and presenting antigens. The chemotactic movement of TSPAN1+ B cells toward the liver of AIH was possibly due to CXCR3 - CXCL10 interaction.